A systematic review with narrative synthesis on medical robotics and laboratory automation in the control of SARS-CoV-2, Ebola and H1N1 (Swine Flu) viruses - Shantani KANNAN; Kannan SUBBARAM; Sheeza ALI; Hemalatha KANNAN (Journal of Health and Social Sciences)
Introduction: Medical robotics is a rapidly growing aspect of the modern health care landscape. The aim of this paper was to review the availability of robotic technology and laboratory automation in the control of SARS-CoV-2, Ebola and H1N1 (Swine Flu) viruses. Methods: A systematic review with narrative synthesis was conducted using the following databases: ME- DLINE / PubMed, SCOPUS, Web of Science, Science Direct and Google Scholar to retrieve studies re- garding the use of robots and automated lab technologies, with appropriate MeSH terms and in accordance with the “Preferred Reporting Items for Systematic reviews and Meta-Analyses” (PRISMA) guidelines. A narrative synthesis was performed to synthesize the findings of the different studies. Results: A total of 250 articles were selected and 30 articles were included in this systematic review. Our findings indicate that robotic technology and automated laboratories have a promising approach, while handling biosafety level – 3 & 4 (BSL-3 & 4) biological agents. In case of epidemics with high case fatality ratio (Ebola virus) or high human-to-human transmission (SARS-CoV-2), healthcare workforce are at high risk. Thus, if robots are employed in such settings, it is possible to minimize intra-hospital transmission of these infections to the highest degree. Discussion and Conclusion: Medical robotics and lab automation may be utilized as a strategic approach in containing the spread of infectious diseases like SARS-CoV-2, Ebola and Swine Flu Pandemic (H1N1). However, in the next future, many clinical trials and further tests are needed to determine the effectiveness of this technology, in order to balance advantages and risk factors involved.